Spatiotemporal Regulation of the Bone Immune Microenvironment via Dam‐Like Biphasic Bionic Periosteum for Bone Regeneration. Issue 1 (14th October 2022) - Xu, Zonghan; Wu, Liang; Tang, Yu; Xi, Kun; Tang, Jincheng; Xu, Yichang; Xu, Jingzhi; Lu, Jian; Guo, Kaijin; Gu, Yong; Chen, Liang
Abstract: The bone immune microenvironment (BIM) regulates bone regeneration and affects the prognosis of fractures. However, there is currently no effective strategy that can precisely modulate macrophage polarization to improve BIM for bone regeneration. Herein, a hybridized biphasic bionic periosteum, inspired by the BIM and functional structure of the natural periosteum, is presented. The gel phase is composed of genipin‐crosslinked carboxymethyl chitosan and collagen self‐assembled hybrid hydrogels, which act as the "dam" to intercept IL‐4 released during the initial burst from the bionic periosteum fiber phase, thus maintaining the moderate inflammatory response of M1 macrophages for mesenchymal stem cell recruitment and vascular sprouting at the acute fracture. With the degradation of the gel phase, released IL‐4 cooperates with collagen to promote the polarization towards M2 macrophages, which reconfigure the local microenvironment by secreting PDGF‐BB and BMP‐2 to improve vascular maturation and osteogenesis twofold. In rat cranial defect models, the controlled regulation of the BIM is validated with the temporal transition of the inflammatory/anti‐inflammatory process to achieve faster and better bone defect repair. This strategy provides a drug delivery system that constructs a coordinated BIM, so as to break through the predicament of the contradiction between immune response and bone tissue regeneration. Abstract : A novel micro‐sol (MS)@carboxymethyl chitosan (CMC)‐collagen (Col) biphasic bionic periosteum is constructed and its feasibility in bone regeneration is tested in the study. The biphasic bionic periosteum can coordinate the conversion of macrophages (M φ ) subtypes through controlled release of interleukin‐4 (IL‐4) and realize the controllable conversion of the inflammatory microenvironment to an anti‐inflammatory microenvironment, resulting in excellent bone defect repair ability.